2016
DOI: 10.1007/s11626-016-0022-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of triamcinolone acetonide and in combination with hyaluronan on canine normal and spontaneous osteoarthritis articular cartilage

Abstract: The purposes of this study were to examine the cartilage degradation effects of triamcinolone acetonide (TA) on normal and osteoarthritic (OA) primary canine chondrocytes and cartilage explants and to examine the cartilage degradation effects of TA in combination with low-molecular-weight hyaluronan (LMWHA). To assess the effects of these drugs on cell culture, 3,[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay and real-time PCR were used to measure chondrotoxicity and determine gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…However, in this study, it was found that the combination treatment with CAR with HA (Comb24 and Comb48) did not decrease chondrotoxicity (and did not increase chondrocyte viability). Similar to our previous study involving OA chondrocyte cultures, co-treatment with HA did not decrease chondrotoxicity caused by CAR (Euppayo et al, 2015), triamcinolone acetonide (Euppayo et al, 2016), dexamethasone (Siengdee et al, 2015) and prednisolone (Siengdee et al, 2015). However, some studies have shown that HA could reduce cytotoxicity on chondrocyte viability after cells were exposed to bupivacaine (Onur, Sitron & Dang, 2013), indomethacin (Hashizume & Mihara, 2009), dexamethasone (Hashizume & Mihara, 2009) and celecoxib (Hashizume & Mihara, 2009).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, in this study, it was found that the combination treatment with CAR with HA (Comb24 and Comb48) did not decrease chondrotoxicity (and did not increase chondrocyte viability). Similar to our previous study involving OA chondrocyte cultures, co-treatment with HA did not decrease chondrotoxicity caused by CAR (Euppayo et al, 2015), triamcinolone acetonide (Euppayo et al, 2016), dexamethasone (Siengdee et al, 2015) and prednisolone (Siengdee et al, 2015). However, some studies have shown that HA could reduce cytotoxicity on chondrocyte viability after cells were exposed to bupivacaine (Onur, Sitron & Dang, 2013), indomethacin (Hashizume & Mihara, 2009), dexamethasone (Hashizume & Mihara, 2009) and celecoxib (Hashizume & Mihara, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…However, HA could lessen the side effects of fluoroquinolones when treatment was given in conjunction with those other drugs (Siengdee et al, 2016). On the contrary, the therapeutic effects of HA could not mitigate the side effects of carprofen (Euppayo et al, 2015), corticosteroid (Siengdee et al, 2015) and triamcinolone acetonide (Euppayo et al, 2016) when subjects were treated with HA at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…In general, controversy on the effect of corticosteroids on joint cartilage is still considerable. Negative effects of corticosteroids on cartilage integrity have been mainly described in vitro, in monocultures of chondrocytes or cartilage tissue explants (Euppayo et al, ; Suntiparpluacha, Tammachote, & Tammachote, ), although loss of safranin‐O positivity was found upon IA injection of TAA‐delivering MSs in healthy joints (Bodick et al, ). However, we showed that while TAA indeed inhibited proteoglycan content of cartilage explants in monoculture, in co‐cultures of cartilage explants with synovial tissue, the same concentration of TAA enhanced proteoglycan synthesis (Beekhuizen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Part III, in vitro studies — There were five studies [ 22 , 23 , 38 40 ], including anabolic gene ( ACAN and COL2A1 ) expression, catabolic gene ( ADAMTS5 , COX-2 , IL-1β , MMP2 , MMP3 , and MMP13 ) expression, and GAG remaining in chondrocyte pellets or cartilage explants.…”
Section: Resultsmentioning
confidence: 99%